PEMBUATAN LARU TEMPE DAN PENGAMATAN KEKUATANNYA SELAMA PENYIMPANAN - Hermana Hermana; Sri Wismaniah Roedjito (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1971)
Pembuatan laru tempe dan pengamatan kekuatannja selama penjimpanan. (Preparation of tempeh mold inoculum and observation on its activity during storage). "Laru" or tempeh mold inoculum can be made by growing tempeh mold on rice or "tiwul" (steamed cassava flour). Mold grown rice or "tiwul" is dried in the sun when the spores are fully mature. It is then ground to powder. The spores may also be taken from the dried rice or "tiwul" by rubbing them off with wheat flour. Rice flour or tapioca may be used as substitutes of wheat flour. The flours are also used to dilute the concentration of the spores in inoculum. Another type of tempeh mold inoculum can be made by grinding dried tempeh into powder. "Laru" made by growing tempeh mold on rice is the best of the three, is easy to be prepared and is inexpensive. The self-life is at least six months when stored in a closed container at room temperature (25°C) Walaupun laru murni tentu sangat baik, cara pembuatan laru murni seperti dikerjakan oleh Yap dan Stanton terlalu sulit dan mahal untuk dilaksanakan oleh pedagang tempe di Indonesia pada masa ini. Pada penelitian ini dicari cara pembuatan laru tempe yang mudal dilakukan dan murah, larunya dapat ditakar dan dapat disimpan lebih lama.